Prevalence and determinants of work-related ocular symptoms among dentists of Bangladesh: A cross-sectional study - Taslima Rafique; Fahima Nasrin Eva; Md. Shah Fattehullah Bhuyan; Shourov Barua; Jyotie Malakar; Arpita Biswangree; Dilruba Alam Chowdhury; Tasin Afrose; Parikshit Dutta; Jannatun Nahar; Disha Mony Dey; Sreshtha Chowdhury; et al. (PLoS ONE, 2025)
Objectives The present study aims to investigate the prevalence of work-related ocular symptoms and their associated factors among Bangladeshi dentists. Methods This cross-sectional study was conducted among 747 practicing dental surgeons working in government and private facilities across Bangladesh. Participants were recruited using snowball sampling, and an online semi-structured questionnaire was used for data collection. The study collected sociodemographic information, clinical practice details, and ocular symptoms-related information. Regarding ocular symptoms, the participants were asked to report the occurrence of common ocular symptoms (e.g., eye itching, eye pain, blurring) in the last month. Results The study found a high prevalence of ocular symptoms among dentists, with the most common being eye itching (46.85%), blurring of vision (41.1%), and eye pain (40.7%). Female dentists were more likely to report ocular symptoms, with males having lower odds of eye pain (AOR: 0.53, 95% CI: 0.40–0.85) and itching (AOR: 0.58, 95% CI: 0.40–0.85). Smoking was a strong predictor of eye pain (AOR: 1.33, 95% CI: 1.19–3.11) and itching (AOR: 1.92, 95% CI: 1.19–3.11). Dentists working > 28 hours per week (AOR: 1.91, 95% CI: 1.07–3.44) and attending >5 patients/day (AOR: 1.51, 95% CI: 1.08–2.12) had higher odds of developing eye pain, while routine ocular checkups were associated with lower odds of eye pain (AOR: 0.62, 95% CI: 0.44–0.89). Conclusion Ocular symptoms are highly prevalent among Bangladeshi dentists, emphasizing the need for regular eye checkups, ergonomic practices, and workload adjustments to mitigate occupational risk factors and protect visual health.